2008
DOI: 10.1523/jneurosci.4274-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition Combines with Excitation to Extend the Operating Range of the OFF Visual Pathway in Daylight

Abstract: Cone signals divide into parallel ON and OFF bipolar cell pathways, which respond to objects brighter or darker than the background and release glutamate onto the corresponding type of ganglion cell. It is assumed that ganglion cell excitatory responses are driven by these bipolar cell synapses. Here, we report an additional mechanism: OFF ganglion cells were driven in part by the removal of synaptic inhibition (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
321
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(342 citation statements)
references
References 85 publications
(135 reference statements)
18
321
0
Order By: Relevance
“…In this revised scheme, intrinsic oscillations in the AII/ cone ON bipolar cells provide the major drive to both amacrine and ganglion cells. In addition, extending the known AII amacrine cell circuit in wt retina (Manookin et al, 2008;Murphy and Rieke, 2008;Münch et al, 2009), we speculate that oscillations in the AII amacrine cells could carry over to the OFF system through gly- cinergic inhibition of the OFF bipolar cells and ganglion cells (Fig. 10).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this revised scheme, intrinsic oscillations in the AII/ cone ON bipolar cells provide the major drive to both amacrine and ganglion cells. In addition, extending the known AII amacrine cell circuit in wt retina (Manookin et al, 2008;Murphy and Rieke, 2008;Münch et al, 2009), we speculate that oscillations in the AII amacrine cells could carry over to the OFF system through gly- cinergic inhibition of the OFF bipolar cells and ganglion cells (Fig. 10).…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, oscillations were not observed in wt AII amacrine cells (n ϭ 4) (Fig. 7 B, D) (Manookin et al, 2008;Murphy and Rieke, 2008;Münch et al, 2009) (but see Veruki and Hartveit, 2002). Figure 7B illustrates the relatively stable baseline of a wt AII amacrine cell.…”
Section: Spontaneous Activity In Rd1 Bipolar Cellsmentioning
confidence: 88%
“…In the guinea pig, pharmacological measurements have suggested that AII amacrine cells carrying signals from cone photoreceptors hyperpolarize to disinhibit Off-type ganglion cells (12). In the salamander retina, disinhibition has been shown in the context of a flash of light (11), where hyperpolarization of GABAergic amacrine cells is thought to delay the truncation of the Off ganglion cell light response.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory transmission to ganglion cells is known to have different effects, including reducing activity (6, 10), or increasing activity through disinhibition (11)(12)(13)(14). Thus, to understand how a particular amacrine cell changes the ganglion cell response, measurements of both the response and transmission of the interneuron must be temporally precise.…”
mentioning
confidence: 99%
See 1 more Smart Citation